Kualitas Sumber Air Minum Masyarakat Kampung Yokiwa Distrik Sentani Timur Secara Bakteriologis - Ima F. Patasik; Daniel Lantang (Jurnal Biologi Papua, 2009)
The aim of this study was to observe the presence of coliform bacteria and the level of contamination in outlet water of Sentani lake, especially in Jaifuri river. The study was done from Januari-April 2009 in 3 sampling areas: outlet of the lake (A), in between outlet and the river (B), and in Jaifuri river (C). Samples then be analized in Biology Laboratory, FMIPA University of Cenderawasih using MPN (Most Probable Number) series 3-3-3. Furthermore, the result then compared with the quality standard of dringking water (Peraturan Menteri Kesehatan RI No 416/MENKES/PER/IX1990). The result showed that coliform of sample A was 9.300 MPN/ 100 ml, sample B was 4.300 MPN/100 ml and sample C was 24.000 MPN/ 100 ml. That condition was above the maximum level of contamination of dringking water (0/100 ml). In addition, the biochemical test showed that Escherichia coli and Klebsiella pneumoniae were found in that water samples.  Key words: Coliform, Escherichia coli, outlet of Sentani lake, Jaifuri river, East Sentani.